Efficient clearance of non-transferrin-bound iron by rat liver. Implications for hepatic iron loading in iron overload states. - Brissot, P (1985)
In hemochromatosis and other disorders associated with iron overload, a significant fraction of the total iron in plasma circulates in the form of low molecular weight complexes not bound to transferrin. Efficient and unregulated clearance of this form of iron by the liver may account for the hepatic iron loading and toxicity that characterize these diseases. We tested this possibility by examining the hepatic removal process for representative iron complexes in the single-pass perfused rat liver. Hepatic uptake of both ferrous and ferric 55Fe from ultrafiltered human serum was found to be highly efficient and effectively irreversible (single-pass extraction of 1 microM iron, 58-75%). Similar high efficiencies were seen for iron complexed to specific physiologic and nonphysiologic coordinators, including histidine, citrate, fructose, oxalate and glutamate, and tricine. Because of lower plasma flow rates, single-pass extraction of these iron complexes in vivo should be even greater. Autoradiography confirmed that most iron had been removed by parenchymal cells. Hepatic removal from Krebs-tricine buffer was saturable with similar kinetic parameters for ferrous and ferric iron (apparent Km, 14-22 microM; V max, 24-38 nmol min-1 g liver-1). These findings suggest that high levels of non-transferrin-bound iron in plasma may be an important cause of hepatic iron loading in iron overload states.